2007
DOI: 10.1136/qshc.2006.019331
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of complications during percutaneous coronary intervention

Abstract: Background: Technological advances have enabled percutaneous coronary intervention (PCI) to be applied with expanding indications. However, escalating costs are of concern. This study assessed the incremental medical costs of major in-hospital procedural complications incurred by patients undergoing PCI. Methods: We considered all patients undergoing elective, urgent, or emergent PCI at Mayo Clinic Rochester between 3/1/1998-3/31/2003 in analyses. Clinical, angiographic, and outcome data were derived from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…All event costs, including direct medical costs of hospitalization due to PCI, costs of drug therapy, and costs associated with events incorporated into the model were derived from publically available sources and are shown in Table . Costs for genotyping were obtained by averaging reported costs from a direct‐to‐consumer Web site for CYP2C19 testing (cost includes testing for CYP2C19 *1 , *2 , *3 , *4 , *5 , *6 , *7 , *8 , and *17 ) and costs derived from Current Procedural Terminology codes associated with molecular testing for the state of Maryland .…”
Section: Methodsmentioning
confidence: 99%
“…All event costs, including direct medical costs of hospitalization due to PCI, costs of drug therapy, and costs associated with events incorporated into the model were derived from publically available sources and are shown in Table . Costs for genotyping were obtained by averaging reported costs from a direct‐to‐consumer Web site for CYP2C19 testing (cost includes testing for CYP2C19 *1 , *2 , *3 , *4 , *5 , *6 , *7 , *8 , and *17 ) and costs derived from Current Procedural Terminology codes associated with molecular testing for the state of Maryland .…”
Section: Methodsmentioning
confidence: 99%
“…Percutaneous coronary intervention complications have been linked to increased consumption of healthcare resources, delays in hospital discharge, and patient dissatisfaction. It was reported that PCI bleeding complications cost an additional US $13,092 and added 4.4 days to a patient's hospitalization, 2 and vascular complications cost an additional US $4,830 and 2.1 hospital days. 3 The incidence of vascular complications ranges from 5.4% to 37%.…”
mentioning
confidence: 98%
“…Cost reduction efforts may target CCL operating costs and/or costs of care outside the CCL. For example, lower stent prices will reduce expenses in the CCL, whereas drug-eluting stents may reduce costs outside the CCL; reducing procedural complications will reduce both in-lab and out-of-lab costs [67,68]. Specific recommendations include the following:…”
Section: Cost Considerationsmentioning
confidence: 99%